Non-western & obsolete instruments - Dearling, Robert, 1933- (Philadelphia : Chelsea House, 2001)
Presents an illustrated introduction to non-Western and obsolete instruments, featuring alphabetically arranged entries that provide descriptions of blown, plucked, banged, and miscellaneous types of instruments, including the alphorn, bagpipes, lute, sansa, anvil, handbells, and others.
Includes index.
6.8
5-8
Keywords: Musical instruments -- History -- Encyclopedias